Resolution of asthmatic symptoms following successful endoscopic resection of tracheal mucoepidermoid carcinoma - Yusof Khan, Abdul Hanif Khan; Mohamed Faisal; Mohd Ali, Razana; Abdul Rahman, Jamalul Azizi (BMJ Publishing Group, 2019)
Mucoepidermoid carcinoma (MEC) is a rare tumour of the trachea accounting for up to 0.2% of reported primary lung malignancy. We report a case of a 54-year-old man, ex-smoker, whose presentation mimicked adult onset asthma with cough and wheezing, which did not respond to conventional treatment. He had occasional haemoptysis and weight loss in which CT scan performed for malignancy screening showed a protruding mass in the distal trachea causing endobronchial obstruction. Bronchoscopic intervention was performed to relieve the obstruction that resulted in resolution of asthmatic symptoms. Histological diagnosis confirmed MEC. This case emphasised the importance of a high index of suspicion in an unusual presentation of a common disease and the pivotal role of bronchoscopic intervention in malignant central airway obstruction.